Exploring the thermal behavior and hydrothermal characteristics of ferrofluid in a complex enclosure under magnetic field and porous media: Influence of surface roughness - Chattopadhyay, Anirban; Goswami, Krishno D.; Pandit, Swapan K.; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2025)
e7 have emerged as a promising medium in numerous technological and biomedical applications, owing to their unique thermal and magnetic properties. In this context, this study aims to explore the thermal behavior and hydrothermal characteristics of ferrofluids in a complex enclosure with a specific focus on the influence of surface roughness. The complex enclosure comprises cold upper and cold right walls with wavy profiles, a heated left flat wall and an adiabatic lower flat wall, with the lower wall moving at a uniform velocity. A kerosene-cobalt ferrofluid saturated porous medium mixture was introduced into the enclosure and the controlling equations are numerically solved using a compact finite difference scheme. Key parameters such as the Richardson number, Reynolds number, Grashof number, Hartmann number, Darcy number, Prandtl number, magnetic field orientation angle and wavy surface amplitude are varied while regulating the ferromagnetic particle volume fraction. Our results, in congruence with existing literature data, demonstrate a striking resemblance. It is found that the magnetic field increases or decreases the thermal performance depending on its strength and orientation. Additionally, the surface roughness of the enclosure plays a crucial role in modulating the hydrothermal characteristics of the ferrofluid. The role of present study includes the development of a highly efficient cooling systems in electronic devices, superior heat exchangers for energy production, and enhancing heat transfer in biomedical applications such as hyperthermia treatment for cancer.
Keywords: Compact scheme; complex enclosure; ferrofluid; MHD; mixed convection; porous media